Systematic Literature Review: Asesmen Matematika Kontekstual Untuk Mengukur Kemampuan Akademik Siswa SMP - Adrian Murkat Gumay; Drajat Friansah; Maria Luthfiana (Proceeding of Silampari Conference of Life Science and Technology, 2026)
Students academic performance in mathematics has remained a major concern, particularly when viewed through the lens of international assessment results. In PISA 2018, Indonesia ranked 73rd out of 79 countries with an average score of 379, while TIMSS results similarly indicate that Indonesian students' mathematical literacy remains relatively low. One of the primary contributing factors is the form of assessment, which has not sufficiently connected mathematical concepts to students' everyday lives. Therefore, contextual mathematics assessment is considered an appropriate approach to measuring students' academic abilities more comprehensively. This study aims to systematically examine various research studies on contextual mathematics assessment and its relationship to the academic abilities of junior high school students, employing a Systematic Literature Review (SLR) method. The review was conducted on 17 relevant scientific articles published between 2020 and 2026, sourced from Google Scholar, Garuda, Sinta, and Publish or Perish. The review process encompassed the stages of identification (32 articles), screening, eligibility assessment, and synthesis. The findings indicate that contextual assessment is capable of strengthening conceptual understanding, higher-order thinking skills (HOTS), and students' mathematical literacy. Nevertheless, the development of assessment instruments that are valid, reliable, and practical remains limited. Consequently, further research is needed to develop more effective contextual mathematics assessments that are aligned with 21st-century learning needs.